2009
DOI: 10.1136/jech.2008.078428
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic status is associated with frailty: the Women's Health and Aging Studies

Abstract: Background-Frailty is a common risk factor for morbidity and mortality in older adults. Although both low socioeconomic status (SES) and frailty are important sources of vulnerability, there is limited research examining their relationship. We sought to determine 1) the extent to which low SES was associated with increased odds of frailty and 2) whether race was associated with frailty, independent of SES.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
110
3
11

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(139 citation statements)
references
References 38 publications
(41 reference statements)
15
110
3
11
Order By: Relevance
“…However, the poverty rate in this state is still 26.6% 9 . In Brazil the public health system provide services to almost all low-income population, defined as annual income of less than US$ 10,000.00 10 . Low income pregnant women have higher rates of preterm labor, lower weight of the newborn and higher maternal mortality compared to women with a higher economic level [11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…However, the poverty rate in this state is still 26.6% 9 . In Brazil the public health system provide services to almost all low-income population, defined as annual income of less than US$ 10,000.00 10 . Low income pregnant women have higher rates of preterm labor, lower weight of the newborn and higher maternal mortality compared to women with a higher economic level [11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…For example, an individual's wealth and the level of neighbourhood deprivation impacts on frailty and mortality but the size and direction of the impact may differ between the sexes (Gu et al, 2009;Lang et al, 2009;Major et al, 2010;Romero-Ortuno, 2014;Woo et al, 2005). Factors such as marital status, education level and social supports have all been reported to impact on male and female frailty (Andrew et al, 2008;Gorman and Read, 2006;Gu et al, 2009;Szanton et al, 2010;Woo et al, 2005).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…In fact, more recently, Fried and coauthors suggested that these factors were related to frailty. 6 An alternative model that took a quantitative approach and defined frailty as the accumulation of deficits was suggested by Rockwood and coworkers. 7,8 They proposed that the risk of becoming frail increased with certain deficits.…”
mentioning
confidence: 99%